The impact of a human papillomavirus (HPV) vaccination campaign on routine primary health service provision and health workers in Tanzania: a controlled before and after study - Katherine E. Gallagher; Tusajigwe Erio; Kathy Baisley; Shelley Lees; Deborah Watson-Jones (BMC, 2018)
Abstract Background The burden of cervical cancer and shortage of screening services in Tanzania confers an urgent need for human papillomavirus (HPV) vaccination. However, the sustainability and impact of another new vaccine campaign in an under-resourced health system requires consideration. We aimed to determine the impact of the government's school-based HPV vaccine campaign in Kilimanjaro region on the provision of routine primary health services and staff workload. Methods Data on daily numbers of consultations were collected from health facility register books in 63 dispensaries and health centres in North-West Tanzania for 20 weeks in 2014. Changes in outpatient, antenatal care (ANC), family planning (FP) and immunisation service activity levels before, during and after the two HPV vaccination campaigns in 2014 in 30 facilities within Kilimanjaro region ('intervention facilities') were compared with changes in activity levels in 33 facilities in Arusha region ('controls'). Qualitative interviews were conducted with health workers in Kilimanjaro region who delivered HPV vaccination and those who remained at the facility during in-school HPV vaccine delivery to explore perceptions of workload and capacity. Results Health facility activity levels were low and very variable in both regions. Controlling for district, facility type, catchment population, clinical staff per 1000 catchment population and the timing of other campaigns, no evidence of a decrease in consultations at the health facility during HPV vaccination week was found across outpatient, ANC, routine immunisation and FP services. However, compared to the average week before and after the campaign, health workers reported longer working hours and patient waiting times, feeling over-stretched and performing duties outside their normal roles whilst colleagues were absent from the facility conducting the HPV vaccine campaign. Conclusion Qualitative interviews with health workers revealed that staff absence from the health facility is common for a number of reasons, including vaccination campaigns. Health workers perceived that the absence of their colleagues increased the workload at the health facility. The numbers of consultations for each service on 'normal days' were low and highly variable and there was no clear detrimental effect of the HPV vaccination campaign on routine health service activity.